New ingredients and alternatives to durum wheat semolina for a high quality dried pasta. (October 2021) - Romano, Annalisa; Ferranti, Pasquale; Gallo, Veronica; Masi, Paolo
Graphical abstract: Highlights: Novel ingredients (plant, ocean and insect) can improve pasta nutritional quality. Minor Triticum species may be healthy and functional ingredient for pasta making. Pasta quality/consumer satisfaction are affected by non-conventional ingredients. Legume flour and hydrocolloids can mimic wheat functionality in gluten-free pasta. Medium levels of legume flour in pasta improve technological and nutritional profile. Abstract : The increasing interest of consumers for food with enhanced nutritional characteristics has spurred industry to look for unconventional raw materials for novel food design. Pasta is a staple food consumed all over the world, and therefore represents an ideal matrix for the enrichment with functional ingredients. Despite durum wheat semolina is the best raw material for Italian-type pasta making, due to its physicochemical, rheological and sensory properties, nutritionally enriched pasta is becoming quite popular among specific segments of consumers. Nowadays, there is a wide choice of ingredients available to modify and improve the nutritional profile of durum wheat semolina pasta. Among them dietary fibre, legume flour, rice, corn, emmer, cricket flour among others. The novel ingredients and process also allow the production of high quality gluten-free pasta for sensitive and celiac consumers categories. The use of alternative ingredients in pasta formulation results in interesting modifications in quality as well as nutritional and sensory characteristics.